Thermal performance of nano-enriched form-stable PCM implanted in a pin finned wall-less heat sink for thermal management application. (15th December 2020) - Reuben Raj, Cyril; Suresh, S.; Vasudevan, Sudharshan; Chandrasekar, M.; Kumar Singh, Vivek; Bhavsar, R.R.
Graphical abstract: Highlights: FS-PCMs implanted in a novel wall-less heat sink for avionics TM system. Synthesis of 1 wt% MWCNT/GnP enriched HMDI cross-linked PEG-6000 as FS-PCMs. Synthesised FS-PCM retained chemical and thermal stability till 1000 cycles. MWCNT and GnP enriched FS-PCMs increased heat conduction by 61.73% and 84.48%. Heat transfer study reveals less thermal difference and better thermal response. Abstract: Integrated and efficient circuitry has become a crucial part of modern technology which urged the necessity in development of efficient and robust Thermal Management (TM) system for its steady operation under higher heat dissipation. Thus the research work aims to analyse the heat transfer performance of a novel wall-less heat sink packed with highly stable synthesised Hexamethylene Diisocyanate cross-linked Polyethylene Glycol-6000 based Form-Stable Phase Change Material (FS-PCM) for its suitability in passive TM systems with chemical and thermal stability till 1000 thermal cycles. An inclusion of 1 wt% (Multi-Wall Carbon Nano Tubes /Graphene nano Platelets) in FS-PCM improved its thermal conductivity by 61.73% (0.448 W/m-K) and 84.48% (0.511 W/m-K) respectively. The characterisation was carried out for its micro and nano structural morphology, elemental composition, chemical composition and thermal properties like thermal degradation, phase transition attributes, specific heat and thermal conductivity via Field Emission Scanning Electron Microscope, Energy Dispersive X-ray Spectroscopy, Carbon Hydrogen Nitrogen analyser, Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis, Differential Scanning Calorimetry and KD2 pro analyser respectively. The transient heat transfer study of square pin finned heat sink was performed under a set of ON/OFF duty cycles for various heat rates with different aspects of FS-PCMs. In addition, the effect of nanoparticle reduced the thermal difference of FS-PCM in heat sink. Furthermore, involvement of FS-PCM in energy storage characteristics was improved reducing the heat sink base temperature to a maximum of 9.77%. Finally, the experimental results were numerically validated using COMSOL software establishing its reliability for real-time avionics TM application.